THE CONCEPT OF TOURISM AND THE HISTORY OF ITS FORMATION - Axmedova Dilfuza Nuriddinovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the concept of tourism, its stages of formation, history, types and analyzes them on the basis of factual examples.